2020
DOI: 10.3389/fpsyg.2020.583868
|View full text |Cite|
|
Sign up to set email alerts
|

A Good Night’s Sleep: Learning About Sleep From Autistic Adolescents’ Personal Accounts

Abstract: BackgroundSleep is a strong predictor of quality of life and has been related to cognitive and behavioral functioning. However, research has shown that most autistic people experience sleep problems throughout their life. The most common sleep problems include sleep onset delay, frequent night-time wakings and shorter total sleep time. Despite the importance of sleep on many domains, it is still unclear from first-hand accounts what helps autistic people to sleep. The purpose of this study is to explore togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Some of the strategies they have found helpful, such as supportive interactions and engaging in fun activities, are outside conventional clinical approaches. This is similar to findings from Pavlopoulou (2020) who elicited personalized accounts of effective sleep strategies from 54 autistic adolescents. Like the strategies described by the youth in our study, the successful sleep strategies identified sometimes aligned with conventional wisdom pertaining to sleep (e.g., relaxation before going to sleep), but sometimes diverged (e.g., control over sensory stimuli at bedtime).…”
Section: Discussionsupporting
confidence: 83%
“…Some of the strategies they have found helpful, such as supportive interactions and engaging in fun activities, are outside conventional clinical approaches. This is similar to findings from Pavlopoulou (2020) who elicited personalized accounts of effective sleep strategies from 54 autistic adolescents. Like the strategies described by the youth in our study, the successful sleep strategies identified sometimes aligned with conventional wisdom pertaining to sleep (e.g., relaxation before going to sleep), but sometimes diverged (e.g., control over sensory stimuli at bedtime).…”
Section: Discussionsupporting
confidence: 83%
“…Thus, there has been very little focus on enjoyment for enjoyment's sake, and what kinds of intrinsic motivation that autistic people (particularly CYP) may get from their hobbies and interests. One approach to understanding the impact of gaming on well-being in CYP from their own perspective is through the Lifeworld Framework (Pavlopoulou, 2020;Pavlopoulou & Dimitriou, 2019). The lifeworld framework is an epistemological framework which emphasizes the importance of a collaborative approach to understanding a young person's personal strengths, challenges and aspirations.…”
Section: What the Present Study Adds?mentioning
confidence: 99%
“…Fortunately, more recently there has been increasing recognition that it is time for change, with autistic advocates, academics and activists insisting that participatory research is the way forward (e.g., Pellicano and Stears, 2011;Milton and Bracher, 2013;Fletcher-Watson et al, 2019;Gowen et al, 2019). Indeed, there are some great examples emerging of collaborations that have involved the autism community in priority-setting and research (e.g., Nicolaidis et al, 2011Nicolaidis et al, , 2013Bertilsdotter Rosqvist, 2019;Crane et al, 2019;Fletcher-Watson et al, 2019;Vincent, 2019;Young et al, 2019;Pavlopoulou, 2020;Pellicano et al, 2020). One gold-standard example of how researchers, autistic people and their allies can effectively collaborate is the "Shaping Autism Research" seminar series (Fletcher-Watson et al, 2019).…”
Section: A Brighter Futurementioning
confidence: 99%
“…Following this, the consultation group created visual aids that were then used for dissemination at a community exhibition alongside panel discussions and workshops involving various members of the autism community (parents, psychologists, autistic people, etc.). By adopting an experience-sensitive participatory approach grounded within the lifeworld framework (see Hemingway et al, 2015 andPavlopoulou, 2020), the authors acknowledged the autistic participants as active agents in research, recognized their autonomy of thought, perspectives and ideas, and facilitated the translation of findings into practice (see Pavlopoulou, 2020).…”
Section: A Brighter Futurementioning
confidence: 99%
See 1 more Smart Citation